Biogas upgrading by chemical absorption using ammonia rich absorbents derived from wastewater - McLeod, Andrew J.; Jefferson, Bruce; McAdam, Ewan J. (IWA Publishing, 2014)
The use of ammonia (NH3) rich wastewaters as an ecological chemical absorption solvent for the selective extraction of carbon dioxide (CO2) during biogas upgrading to ‘biomethane’ has been studied. Aqueous ammonia absorbents of up to 10,000 gNH3 m−3 demonstrated CO2 absorption rates higher than recorded in the literature for packed columns using 20,000–80,000 g NH3 m−3 which can be ascribed to the process intensification provided by the hollow fibre membrane contactor used in this study to support absorption. Centrifuge return liquors (2325 g m−3 ionised ammonium, NH4+) and a regenerant (477 gNH4+ m−3) produced from a cationic ion exchanger used to harvest NH4+ from crude wastewater were also tested. Carbon dioxide fluxes measured for both wastewaters compared reasonably with analogue ammonia absorption solvents of equivalent NH3 concentration. Importantly, this demonstrates that ammonia rich wastewaters can facilitate chemically enhanced CO2 separation which eliminates the need for costly exogenic chemicals or complex chemical handling which are critical barriers to implementation of chemical absorption. When testing NH3 analogues, the potential to recover the reaction product ammonium bicarbonate (NH4HCO3) in crystalline form was also illustrated. This is significant as it suggests a new pathway for ammonia separation which avoids biological nitrification and produces ammonia stabilised into a commercially viable fertiliser (NH4HCO3). However, in real ammonia rich wastewaters, sodium bicarbonate and calcium carbonate were preferentially formed over NH4HCO3 although it is proposed that NH4HCO3 can be preferentially formed by manipulating both ion exchange and absorbent chemistry.
Keywords: Carbon dioxide sequestration; Crystallisation; Gas/liquid contactor; Chemical scrubbing